Dynamic capital structure in China: Determinants and adjustment speed - Yang, Y.; Albaity, M.; Hassan, C.H. (LLC CPC Business Perspectives, 2015)
This paper examines the determinants and adjustment speed of capital structure by using a dynamic panel data, two-step system GMM estimator with the latest data covering the years 2008-2013 in China. The results present a significant difference in the determinants and adjustment speed of capital structure compared to past studies. The authors find that firms adjust debt ratio towards leverage targets at speeds of 37% per annum, yielding a half-life of 1.52 years. Next, it is found that the profitability is no longer a core determinant of capital structure in Chinese listed firms. In addition, the results point out that the capital structure decision is not only affected by financial variables, but is also significantly influenced by human resource factors.